Tracing the origin of Argentine Malbec wines by sensometrics - Urvieta, Roy Alexander (2024)
The study of terroir, increasingly popular in scientific circles, remains a challenging field, particularly in terms of sensory analysis. This paper summarizes our own contribution to the field—an approach for tracing the typicity of wines by sensometrics, using the Malbec variety as a case study. This largescale research fingerprinted 81 wines from 29 parcels from highly contrasting environments (varying climate, elevation, and soils), produced under standardized conditions in three consecutive vintages. Wines were evaluated through descriptive sensory analysis (DA) by a trained panel, and sensory descriptors were associated with different size geographic scales (zones, departments, and Geographic Indications (GIs)). The application of different sensometric tools allowed us to describe the typicity of wines and discriminate each region, proposing a novel methodology for the comprehensive evaluation of terroir from a sensory viewpoint. The vintage effect was very strong at the departmental and GI level, with aroma, taste and mouthfeel descriptors varying annually. However, certain origin descriptors remained consistent, providing insight into the typicity of Malbec. Considering the extension of the experimental study performed, this methodology provides a proof of concept for understanding both terroir and vintage effects from a sensorial perspective, offering wine producers and consumers a clear message backed by scientific evidence.